Micro-bubble dispersion in a two-dimensional mixing layer. (20th June 2008) - Yang, Xiaogang; Li, Li; Rielly, Chris; Huang, Xiaobing; , Zoubir Zouaoui
Dispersion of microbubbles (db < 100 ?m) in a turbulent mixing layer was investigated numerically using a Discrete Vortex Modelling (DVM) while two-way interaction between the dilute dispersed cloud of microbubbles and free-shear layer was taken into consideration. The emphasis of this study is to examine the instantaneous dispersion features of microbubbles entrained by large-scale vortex structures embedded in the free-shear layer, and the effect of interphase momentum coupling on the evolution of the large-scale vortex structures due to the presence of the microbubbles. It was found that the laterally local void fraction profiles achieve similarity conditions downstream of the mixing layer. The simulation revealed that the growth rate of the lateral void fractions is similar to those of the velocity thickness but the lateral void fractions spread greater than the velocity thickness. The correlations between the local void fractions and local vorticity indicated that there is not prominent enhancement of the local void fraction in the centre of the large-scale vortices. In the numerical modelling, two important parameters, drag and lift coefficients in the equation of motion, were also assessed.